Pengaruh senam nifas terhadap penurunan tinggi fundus uteri pada ibu post partum di RSUD Wonosari - Erwita Dina Kumalasari; Suherni Suherni; Heni Puji Wahyuningsih (Jurnal Kesehatan Ibu dan Anak, 2012)
WHO estimates that 150.000 women die every day due to post-partum hemorrhage. SDKI (2007) reported Maternal mortality rate (MMR) in Indonesia 228/100.000 live births. MMR in provinces DIY (2011) 125 / 1OO. live births and the highest in the district GunungKidul 161/1OO.OOO live births. The main causes of maternal deaths are due to postpartum hemorrhage uterine atony. incidence of postpartum hemorrhage in Wonosari hospital increased from 6,51% in 2009to 7,21% in 2010. Gymnastics childbirth can prevent postpartum hemorrhage. Objective is known the influence of exercise postpartum to decrease fundal height in early postpartum mother in Wonosari Hospital in 2012. Methods: this type of True Experiment study, pretest - posttest design with control group. The population is 80 spontaneous postpartum postpartum mothers who gave birth in Wonosari Gunungkidul Hospital. Number of sampel 48 people were taken to the consecutive sampling technique and were divided into experimental and control groups in both primiparous an multiparous respectively 12 people. Data were analyzed by univariate formula percentages, bivariate analysis to t-test test, and multivariate analysis with ANOVA test. Result : The average decrease in TFIJ maternal postpartum primiparous and multiparous in Wonosari hospital ever happened on day -3. The test results paired t -test on primiparous and multiparous before and after child birth exercises known p-value 0,000. The results of independent sample t - test test between primiparous and multiparous who did and did not do gymnastics puerperal known value of t = 6,450 and p-value = A,000. The test result of multivariate with ANOVA test known p-value = 0,143> 0,05.